Experimental Investigations of the Process of Carbonate Fracture Dissolution Enlargement under Reservoir Temperature and Pressure Conditions - Jingxia Wang; Qingchun Yu (Geofluids)
Karst is a central focus in the field of carbonate reservoir geology. Fracture dissolution enlargement is an important mechanism for the formation of high-quality reservoirs. This study performed four carbonate fracture dissolution enlargement (CFDE) experiments under a confining pressure of 20 MPa, and temperatures ranged from 40 to 60°C. CO2-saturated deionized water was injected into artificial carbonate fractures at approximately 11.5 ml/h for 96, 208, 216, and 216 hours. The water flowing out of the fractures was sampled every 8 h to monitor the concentration of Ca2+. SEM photomicrographs and 3D laser scanning images were taken before and after the CFDE experiments to observe the dissolution process of the fracture surfaces. After the CFDE experiment, the hydraulic apertures (Bh) of sample 1 (S1), sample 3 (S3), and sample 4 (S4) were enlarged by 3.4, 1.4, and 1.2 times, respectively. The aperture of sample 2 (S2) was slightly reduced in the early stage of the experiment. The experimental results of this study demonstrate that Bh can be divided into three categories as a function of time: S type, logarithmic type, and polynomial type. The laboratory dissolution rate of S1, S2, S3, and S4 were 2.50 × 10−6, 3.11 × 10−6, 2.70 × 10−6, and 3.04 × 10−6 mol/m2/s. The pattern of fracture dissolution is closely related to the Peclet and Damkohler numbers. The dissolution processes of high Peclet and Damkohler numbers lead to a pattern of obvious channelization. The Peclet and Damkohler numbers of the S3 CFDE experiment were the highest, and the channelizing dissolution is the most notable in S3 of the four fractures. A dissolution process at low temperature has a higher Peclet number and thus leads to obvious channelizing dissolution. Mineral heterogeneities in the rock also play a significant role in channelizing dissolution. A preferential channel typically develops in places where bioclasts are accumulated or the calcite veins are distributed.